A Model of Optimal Time-of-Day Pricing of Electricity under Diverse Welfare Assumptions - Pillai N, Vijayamohanan (Asian Journal of Energy Transformation and Conservation, 2014)
An important feature of an electric power system is that its customer's load varies greatly at random according to time of day, and day of season. Time-of-day pricing of electricity is an indirect load management against such variable demand according to which electricity is charged in relation to the time-differential cost of supply. The present study is an attempt at modeling seasonal time-differential pricing of electricity. The static, deterministic model that we present incorporates diverse technology, as well as soft deterministic equivalents of chance constraints representing stochastic demand and inflows. The model is solved for two types of power systems – pure hydro and hydro-thermal – under the umbrellas of four structural assumptions – first best, second-best, monopoly and constrained monopoly.